In the house of the wicked : a Remy Chandler novel - Tom Sniegoski (Roc, 2012)
Annotation: PI Remy Chandler has always been able to rely on his angelic powers when the situation called for it. But now his human and angelic natures are sharing the same space, and Remy can feel himself becoming more and more volatile.